Main land use planning approaches to structural elements local ecological network - Tretiak, V.; Hun'ko, L. (Land Management, Cadastre and Land Monitoring, 2017)
In modern conditions of social development, changes in land eco-system of economic relations in Ukraine, the problem of providing conditions for the creation of sustainable land use and creation of protected areas get the status of special urgency. Ideology establishment of ecological networks became logical continuation of environmental thought in general.Considering the methodological approach to the establishment of ecological networks we can constitute, that it is an environmental frame of spatial infrastructure, land conservation and environmental areas, major part of land is the basis of the structural elements of ecological network.Designing an ecological network is made through developing regional schemes of Econet formation, regional and local schemes for establishing an ecological network areas, settlements and other areas.Land Management uses design of structural elements of the ecological network in the village council, as a rule, begins with ecological and landscape mikrozonationof the village council, held during the preparatory work for the land drafting and finishing the formation of environmentally homogeneous regions, which represents the tied system components of ecological network, environmental measures in the form of local environmental restrictions (encumbrances) to use land and other natural resources. Additionally, there are some project organization and territorial measures that increase the sustainability area, such as: key, binders, buffer areas and renewable ecological network.Land management projects on the formation of structural elements of ecological network as territorial restrictions (encumbrances) in land are used within the territories Councils determined the location and size of land:- Protection zones around especially valuable natural objects of cultural heritage, meteorological stations, etc. in order to protect them from adverse human impacts;- Protection zones along telecommunication lines, power, land transport, around industrial facilities to ensure normal conditions and reduce their impact on people and the environment, adjacent land and other natural objects;- Sanitary protection zones around facilities that are open and underground water sources, water intake and water treatment plants, water pipes, facilities and other recreational purposes, for their sanitary-epidemiological protection;- Buffer zones around facilities that are sources of harmful substances, odors, increased levels of noise, vibration, ultrasonic and electromagnetic waves, electronic fields, ionizing radiation, etc., to the separation of objects from residential buildings;- Areas of special treatment of land use;- Valuable land and other natural resources;- Areas that protect land from erosion, landslides, flooding, waterlogging, salinization, overroasting, seals, industrial waste pollution, chemical and radioactive substances and other adverse natural and anthropogenic processes;- Other limitations and encumbrances in land use by the legislation of Ukraine.Ultimately, the design of the structural elements of the ecological network is forming local areas as local environmental restrictions (encumbrances) to use land and other natural resources.Keywords: land use, ecological networks, land planning, the key area, landscapes.